Uji Aktivitas Antikolesterol Ekstrak Etanol Daun Gedi (Abelmoschus Manihot L. Medik) Secara In Vitro - Ilyas, Andi Nurjayanti; Rahmawati, Rahmawati; Widiastuti, Harti (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Lifestyle changes, including eating patterns, have caused traditional diets to shift to western diets such as fast foods that contain lots of calories, fat, and cholesterol. One of the plants that are often used by the community as medicine is Gedi (Abelmoschus Manihot (L.) Medik). Gedi (Abelmoschus Manihot (L.) Medik) leaves are empirically used to treat kidney pain, reduce cholesterol, and ulcers. Gedi (Abelmoschus Manihot (L.) Medik) leaves contain compounds that have the efficacy of flavonoids that can be used as cholesterol-lowering agents. This study aims to determine the anti-cholesterol activity of Gedi leaf extract (Abelmoschus Manihot (L.) Medik) in vitro and determine the EC50 value. Samples were extracted by maceration method using 96% ethanol solvent with 9% extract extraction obtained. The extract obtained was analyzed anticolesterol activity by the Lieberman-Burchard method of anhydrous acetic acid and concentrated sulfuric acid using UV-Vis spectrophotometer measurements with a maximum wavelength of 666.97 nm. Ethanol extract of gedi leaves (Abelmoschus Manihot (L.) Medik) has anti-cholesterol activity in vitro. EC50 value of gedi leaf extract (Abelmoschus Manihot (L.) Medik) that is equal to 5007.5 ppm. Research conclusions that at a concentration of 5007.5 ppm can reduce 50% of initial cholesterol. It is recommended to use gedi leaf ethanol extract as medical therapy.